2017
DOI: 10.1128/cvi.00563-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Immunization with a Band-Aid Prevents Experimental Otitis Media in a Polymicrobial Model

Abstract: Otitis media (OM) is a common pediatric disease, and nontypeable Haemophilus influenzae (NTHI) is the predominant pathogen in chronic OM, recurrent OM, and OM associated with treatment failure. OM is also a polymicrobial disease, wherein an upper respiratory tract viral infection predisposes to ascension of NTHI from the nasopharynx, the site of colonization, to the normally sterile middle ear, resulting in disease. Using a clinically relevant viral-bacterial coinfection model of NTHIinduced OM, we performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
(98 reference statements)
1
24
0
Order By: Relevance
“…However, there was a consistent increase in mucosal biofilm burden from 2 to 5 days post challenge and 5 to 14 days post challenge, irrespective of modA2 status. These results were similar to biofilm formation reported during experimental otitis media induced by other NTHi strains (Hong et al, 2009(Hong et al, , 2019Novotny et al, 2017). Representative images of middle ears challenged with the modA2 OFF or modA2 ON variants are shown in Figure 1C.…”
Section: Nthi Strain 723 Locked Variants Induce Otitis Mediasupporting
confidence: 86%
“…However, there was a consistent increase in mucosal biofilm burden from 2 to 5 days post challenge and 5 to 14 days post challenge, irrespective of modA2 status. These results were similar to biofilm formation reported during experimental otitis media induced by other NTHi strains (Hong et al, 2009(Hong et al, , 2019Novotny et al, 2017). Representative images of middle ears challenged with the modA2 OFF or modA2 ON variants are shown in Figure 1C.…”
Section: Nthi Strain 723 Locked Variants Induce Otitis Mediasupporting
confidence: 86%
“…An established adenovirus-NTHI polymicrobial challenge model [32] was employed to assess efficacy of the tip chimeric peptide when delivered as a pre-clinical vaccine antigen. Chinchillas were randomly divided into three cohorts of eight animals each based on body weight and immunised by rubbing vaccine formulations on to the unabraded skin behind each pinna (post-auricular region) [33].…”
Section: Viral-bacterial Co-infection Model Of Experimental Nthi-indumentioning
confidence: 99%
“…This superinfection model is designed to mimic "My child gets a cold, then a week later has an ear infection". Thus, animals were first actively immunised with the tip or tail chimeric peptide to induce the appropriate immune response [31,33,35,38]. Subsequently, chinchillas were challenged first with adenovirus, then 7-days later with NTHI, after which they were monitored for relative development of ascending OM.…”
Section: Pre-clinical Efficacy Of the Tip Chimeric Peptide After Actimentioning
confidence: 99%
“…In this approach, vaccines against major matrix components are administered after the identification of a persistent infection. Recent studies have shown that these vaccines may stimulate the immune system to disperse the biofilm through sequestration of matrix materials 210 , 211 . For S. aureus , therapeutic use of a conjugate capsular polysaccharide and protein vaccine conferred protection in a rat model of osteomyelitis 212 .…”
Section: Targeting the Host Response Against Biofilmsmentioning
confidence: 99%